Life satisfaction in urban China: components and determinants - Lina Song; Simon Appleton (Institute for the Study of Labor (IZA), 2008)
Survey data from urban China in 2002 show levels of life satisfaction to be low, but not exceptionally so, by international comparison. Many of the determinants of life satisfaction in urban China appear comparable to those for people in other countries. These include, inter alia, unemployment, income, marriage, sex, health and age. Communist Party membership and political participation raise life satisfaction. People appear fairly satisfied with economic growth and low inflation, and this contributes to their overall life satisfaction. There is dissatisfaction over pollution, but this - like job insecurity - does not appear to impact on life satisfaction.
urn:nbn:de:101:1-2008041625
Keywords: I31; 330; Life satisfaction; happiness; economic growth; unemployment; China; Lebenszufriedenheit; Lebensstandard; Stadtsoziologie; Wirtschaftswachstum; Arbeitslosigkeit; China